Weather Based Information System using IoT and Cloud Computing - Varghese, Aneeta (IJRDO -Journal of Computer Science Engineering, 2015)
Internet of things connect physical world, interact with them and compute the inputs obtained from the physical scenario. Weather based Information System using IoT and Cloud Computing adopts both the advantages of cloud computing and internet of things. The proposed system uses sensor network for the data acquisition and cloud computing platform for storage and processing. Big data is a big concern to internet of things, which is impossible to handle. The proposed system solves the problem by storing the enormous amount of data in cloud provided datacenters and analyze the large amount of data using k medoid clustering algorithm. K medoid algorithm outperforms other clustering algorithm when the data consists of outliers and noise.